Ensuring environmental sustainability in the printing industry - Che, Akimbom Michael (2011)
Environmental sustainability has come a long way and has been defined in many different ways. The focal point of each definition is countering the depletion of natural resources or the restoration of scarce natural resources for future generations. Approaching this issue has not been thesame in every industry. The main focus of this thesis was to find out the contribution of eco-printing towards environmental sustainability in the printing industry with the case of Uppsala Nya Tidning AB. It focused on the following specific objectives.